CONCEPTUAL METAPHOR IN THE LYRICS OF THE SONG SOUL MANTRA BY AVIWKILA AS A COGNITIVE LINGUISTIC STUDY OF LIFE MOTIVATION NARRATIVE - Wicaksono, Helmi; Sari, Ifit Novita; Santoso, Anang; Martutik, Martutik (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This study aims to analyze conceptual metaphors in the lyrics of the song Mantra Jiwa by Aviwkila as a life motivation narrative through a cognitive linguistic approach. The research method used is descriptive qualitative. This study identifies structural, ontological, and orientational metaphors and their contributions to building motivational narratives. The findings of the study reveal that the lyrics of the song Soul Mantra by Aviwkila use conceptual metaphors to arouse emotional and conceptual involvement, which fosters a motivational perspective. This study enriches the understanding of metaphorical language in popular music and its cognitive impact.